2012
DOI: 10.1242/jeb.070904
|View full text |Cite
|
Sign up to set email alerts
|

Evoked-potential audiogram of an Indo-Pacific humpback dolphin (Sousa chinensis)

Abstract: SUMMARYAn evoked-potential audiogram was measured for an Indo-Pacific humpback dolphin (Sousa chinensis) living in the dolphinarium of Nanning Zoo, China. Rhythmic 20ms pip trains composed of cosine-enveloped 0.25ms tone pips at a pip rate of 1kHz were presented as sound stimuli. The dolphin was trained to remain still at the water surface and to wear soft latex suction-cup EEG electrodes used to measure the animalʼs envelope-following evoked potentials to the sound stimuli. Responses to 1000 rhythmic 20ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…Three suction-cup electroencephalography (EEG) electrodes were non-invasively attached to the back of the dolphin for the AEP recording. Examination of electrical noise before the hearing experiment confirmed that the electrical noise level for the AEP recording was comparable to that in our previous study (Li et al, 2012). The background acoustic noise in the experimental pool was recorded before the hearing measurement commenced and when the water depth in the pool was ~2.5m.…”
Section: Hearing Measurementsupporting
confidence: 81%
See 4 more Smart Citations
“…Three suction-cup electroencephalography (EEG) electrodes were non-invasively attached to the back of the dolphin for the AEP recording. Examination of electrical noise before the hearing experiment confirmed that the electrical noise level for the AEP recording was comparable to that in our previous study (Li et al, 2012). The background acoustic noise in the experimental pool was recorded before the hearing measurement commenced and when the water depth in the pool was ~2.5m.…”
Section: Hearing Measurementsupporting
confidence: 81%
“…To better evaluate the dolphin's hearing, its echolocation clicks were also recorded on 15 April 2012. Both the hearing and echolocation clicks of the present subject were compared with those of a conspecific younger male, ~13years old, which was rescued from stranding on the coast of Beihai Bay, China (Fig.1B), in August 2007 (see Li et al, 2012). The methodology and equipment used for the two dolphins was the same or comparable.…”
Section: Subjectmentioning
confidence: 99%
See 3 more Smart Citations